INVENTARISASI JAMUR TINGKAT TINGGI DI KAWASAN CAGAR ALAM LEMBAH ANAI KABUPATEN TANAH DATAR SUMATERA BARAT - Jusana, Suci Pebra; Fifendy, Mades; Periadnadi, Periadnadi (STKIP PGRI Sumbar, 2013)
AbstrakÂ Mushroom is organism of eukariot generally have many various and size. Mushroom have external form in the form of big sized fruit body so that can perceive by eyes directly. Mushroom of is include organism of heterotrof, that is organism which is life base on other organism or base on available organic materials around him. Mushroom do not have chlorophyll, berkembangbiak sexually and or by aseksual. Lembah Anaisâarea have elms, tree anakan which still nature and semaian anakan very meeting and also damp of air so that represent appropriate habitat for the growth of mushroom, so reseacher do the research about